A STRESS-RESPONSIVE NAC1-Regulated Protein Phosphatase Gene Rice Protein Phosphatase18 Modulates Drought and Oxidative Stress Tolerance through Abscisic Acid-Independent Reactive Oxygen Species Scavenging in Rice . Issue 4 (15th October 2014) - You, Jun; Zong, Wei; Hu, Honghong; Li, Xianghua; Xiao, Jinghua; Xiong, Lizhong
Abstract : A phosphatase gene and its associated transcription factor affect drought and oxidation stress tolerance independent of abscisic acid . Abstract: Plants respond to abiotic stresses through a complexity of signaling pathways, and the dephosphorylation mediated by protein phosphatase (PP) is an important event in this process. We identified a rice ( Oryza sativa ) PP2C gene, OsPP18, as a STRESS-RESPONSIVE NAC1 (SNAC1)-regulated downstream gene. The ospp18 mutant was more sensitive than wild-type plants to drought stress at both the seedling and panicle development stages. Rice plants with OsPP18 suppressed through artificial microRNA were also hypersensitive to drought stress. Microarray analysis of the mutant revealed that genes encoding reactive oxygen species (ROS ) scavenging enzymes were down-regulated in the ospp18 mutant, and the mutant exhibited reduced activities of ROS scavenging enzymes and increased sensitivity to oxidative stresses. Overexpression of OsPP18 in rice led to enhanced osmotic and oxidative stress tolerance. The expression of OsPP18 was induced by drought stress but not induced by abscisic acid (ABA ). Although OsPP18 is a typical PP2C with enzymatic activity, it did not interact with SNF1-RELATED PROTEIN KINASE2 protein kinases, which function in ABA signaling. Meanwhile, the expression of ABA -responsive genes was not affected in the ospp18 mutant, and the ABA sensitivities of the ospp18 mutant and OsPP18 -overexpressing plants were also not altered. Together, these findings suggest that OsPP18 is a unique PP2C gene that is regulated by SNAC1 and confers drought and oxidative stress tolerance by regulating ROS homeostasis through ABA -independent pathways.